2022
DOI: 10.3390/su14094929
|View full text |Cite
|
Sign up to set email alerts
|

Cooling the City? A Scientometric Study on Urban Green and Blue Infrastructure and Climate Change-Induced Public Health Effects

Abstract: Climate change causes global effects on multiple levels. The anthropogenic input of greenhouse gases increases the atmospheric mean temperature. It furthermore leads to a higher probability of extreme weather events (e.g., heat waves, floods) and thus strongly impacts the habitats of humans, animals, and plants. Against this background, research and innovation activities are increasingly focusing on potential health-related aspects and feasible adaptation and mitigation strategies. Progressing urbanization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Xiamen City has coastlines, numerous lakes, and dense river networks. Water bodies not only bring cooling effect to their surroundings ( 67 , 68 ), but also affect the spatial distribution of their surrounding heat vulnerability ( 82 ), which was confirmed in our findings. We found that Maluan Bay, Wuyuan Bay, Yundang Lake and the coast of Xiamen Island were significant low UHV areas, in fact, during our local investigation, we found these areas are also livable areas with beautiful ecological environment in Xiamen City.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Xiamen City has coastlines, numerous lakes, and dense river networks. Water bodies not only bring cooling effect to their surroundings ( 67 , 68 ), but also affect the spatial distribution of their surrounding heat vulnerability ( 82 ), which was confirmed in our findings. We found that Maluan Bay, Wuyuan Bay, Yundang Lake and the coast of Xiamen Island were significant low UHV areas, in fact, during our local investigation, we found these areas are also livable areas with beautiful ecological environment in Xiamen City.…”
Section: Discussionsupporting
confidence: 87%
“…Elevation is the main natural factor influencing the population distribution in China, especially in the eastern part of the country, where the population size at high altitude is small ( 66 ) and consequently the probability of heat exposure is low. Lakes, rivers, coasts, bays are confirmed to have significant cooling effect ( 67 , 68 ), so in this study different distances from these areas were used to reflect differences in the heat susceptibility attributes of the urban system. Combining the characteristics of coastal metropolis, land cover, elevation, water bodies, and coastlines were selected as indicators for measuring urban heat susceptibility.…”
Section: Methodsmentioning
confidence: 99%
“…A wide variety of strategies can be implemented for this purpose. They range from integrated and sustainable rainwater management, the broad implementation of various climate-effective nature-based solutions, and the implementation of high-quality urban green spaces to various specifications regarding open space design [36]. Above allfor the microclimatic optimization of the city-specifications regarding albedo, minimum structural thicknesses of substrates, and a minimum area that may not be sealed or built on are important [84].…”
Section: Discussionmentioning
confidence: 99%
“…Scientists agree that there is an urgent need for action nowadays; the most effective strategy against the urban heat island effect is to enlarge urban green and water areas or to further expand already existing green and blue infrastructure in the private and the public sphere [36,72]. Green and blue infrastructure can support climate change adaptation and mitigation, biodiversity loss, and the promotion of health and well-being simultaneously.…”
Section: Biophilia Through Spatial Layout and Viewsmentioning
confidence: 99%
See 1 more Smart Citation